Melasma and assessment of the quality of life in Brazilian women - Juliana Kida Ikino; Daniel Holthausen Nunes; Vanessa Priscilla Martins da Silva; Tania Silvia Fröde; Mariana Mazzochi Sens (Sociedade Brasileira de Dermatologia, 2015)
BACKGROUND: Melasma is a chronic, acquired hyperpigmentation disease on sun-exposed areas of the skin, which affects patients' quality of life. OBJECTIVE: To assess the impact on the quality of life of women living in Florianópolis, Brazil, through questionnaire (MelasQol), and investigate the clinical aspects and risk factors for melasma, correlating them with the MelasQol scores. METHODS: This study was performed on 51 melasma patients cared for at the University Hospital of the Universidade Federal de Santa Catarina. The variables included were: age, gender, age of onset of melasma, Fitzpatrick phototype (I-VI), duration and family history of melasma, onset of melasma during pregnancy, use of hormonal contraceptive, thyroid disorder and distribution of melasma. The MelasQoL questionnaire, validated for Brazilian Portuguese (MelasQoL-BP), was applied. RESULTS: The mean age was 38.43±6.75 years. All patients were women. The most common Fitzpatrick skin phototypes were III (49.02%) and IV (33.33%). Melasma had a mean age of onset of 29.18±7.05 years and a mean duration of 9.25±6.18 years. The majority of patients did not have familial history of melasma (50.98%). Melasma onset was associated with pregnancy (45.10%). The MelasQoL-BP analysis revealed significant emotional impact on patients, such as feeling bothered (94.11%), frustrated and embarrassed (64.71%), and depressed (52.94%) about their skin appearance, as well as unattractive (78.43%). No social impact was observed (P>0.05). CONCLUSION: Melasma has a strong emotional impact on quality of life, resulting especially from feelings about skin appearance.